Medical and social significance and calculation of the economic burden of axial spondyloarthritis in the Russian Federation - A. M. Lila; T. V. Dubinina; R. O. Dreval; S. А. Lapshina; A. N. Zabotina (Современная ревматология)
Objective: to assess the economic burden of ankylosing spondylitis (AS) and non-radiological axial spondyloarthritis (nr-axSpA) in the Russian Federation, as well as the availability and economic prospects for more complete provision of biological disease-modifying antirheumatic drugs (bDMARDs) to patients with AS and nr-axSpA.Patients and methods. The prevalence of AS and nr-axSpA and organizational aspects of providing with bDMARDs to this category of patients were analyzed.A variant model has been developed in Microsoft Excel, allows to calculate the indicators of the economic burden of AS and nr-axSpA in the Russian Federation, taking into account the economic losses associated with disability, as well as the low availability of bDMARDs. During study preparation, data from real clinical practice and the opinions of experts in the field of AS from various regions of the Russian Federation were studied.The economic burden was calculated as the sum of direct and indirect costs per patient and the population. Additionally, the specific economic burden per capita was determined.Results and discussion. According to expert estimates, the prevalence of AS and nr-axSpA today is 105.0 and 33.2 thousand people, respectively.The current economic burden of the AS for 2019 is estimated at 21.9 billion rubles per population, or 395.5 thousand rubles for 1 patient. The ratio of direct and indirect costs was 1:4, i.e. 4.7 billion rubles – direct costs (84.3 thousand rubles per 1 patient) and 17.2 billion rubles – indirect costs (311.2 thousand rubles per 1 patient). The burden per capita – 149 rubles.Nr-axSpA's current economic burden in 2019 reached 3.0 billion rubles, or 182.9 thousand rubles for 1 patient. The ratio of direct and indirect costs is estimated as 2:5, or 0.9 billion rubles – direct costs (53.0 thousand rubles per 1 patient) and 2.2 billion rubles – indirect costs (130.0 thousand rubles per 1 patient). The burden per capita – 21 rubles.Conclusion. The economic burden of AS and nr-axSpA can be reduced by providing patients with bDMARDs in the required amount: 15% of patients with AS and 10% with nr-axSpA. Due to the imperfection of the regulatory framework, patients with nr-axSpA experience serious difficulties in receiving this therapy within the framework of preferential drug coverage and compulsory health insurance. With the provision of bDMARDs for about 15 and 10% of patients with AS and nr-axSpA, respectively, on the horizon of 5 years, a decrease in disability by 75% and temporary disability by 60% is expected. At the same time, the economic burden for 5 years will decrease by about 40% for each nosology.